TEACHING TERMINAL VOCABULARY OF MODERN EASTERN ARMENIAN DUE TO THE APPLICATION OF MODERN METHOD GUS (EDUCATION IN THE 21ST CENTURY, 2025)
The present article aims at substantiating the thesis that the vocabulary of Grabar is one of the main sources for almost all the terminological vocabulary layers. There is no doubt that over the centuries some words have penetrated into the early Armenian language from the Indo-European vocabulary through internal borrowings, which have later passed into the Grabar vocabulary. Thanks to the ancient borrowings, the vocabulary of Grabar terms was enriched and switched to the Middle Armenian language, and as a result of changing phrases, some of them were translated into Eastern Armenian. Therefore, the novelty of this study is due to the fact that it is justified and proposed in order to make the university study of terminological vocabulary by specialization more effective and purposeful at the Armenian language classes, also to be guided by a new approach proposed by us, that is, to conduct the study of the terminological vocabulary in accordance with an up-to-date GUS method, which supposes a study parallel with their word formulating, genealogical, etymological and semantic research. The relevance of the article is due to the expedient development of effective methods for studying terminological vocabulary in the field of higher education and the need of seeking new ways to submit them.As a result of the investigation, we came to the conclusion that the terminological vocabulary originated in the Indo-European proto-language passed into the Grabar vocabulary through internal borrowing, which was enriched with newly created terms, supplemented with lexical turns specific to the Armenian language, patterns of word complexity, as well as ancient external borrowings. A certain part of the vocabulary of Grabar formed the core of the terminological system of the modern Armenian language through reinterpretation and generalization. With the development of science, new and newest terminological borrowings also replenish the terminological dictionary of the modern Eastern Armenian language. The peculiarity of applying the GUS method in this very case is that the component “know” is provided by school education, and the component “I want to know, I have learnt” is replenished by the higher educational system.The teaching methods of terminology in the field of higher education system include both theoretical and practical components, including lectures, seminars, practical classes, application of different technologies, group work and scientific research activity. Teaching methods contribute to the development of students' comprehensive knowledge and skills, enhancing their success in the fields of terminological studies and research work.
Keywords: Study of terms; teaching method GUS (KWL table or KWL chart); Grabar's vocabulary; terminological dictionary of the modern Eastern Armenian language; change of meaning; termination; neologisms of terms